Learning, cognitive, and attentional problems in adolescents born small for gestational age. - O'Keeffe MJ; O'Callaghan M; Williams GM; Najman JM; Bor W (Pediatrics)
OBJECTIVE: To determine whether the presence, severity, or symmetry of growth restriction in term infants is an independent risk factor for learning, cognitive, and attentional problems in adolescence. METHODS: A total of 7388 term infants have been followed prospectively since birth. At 14 years, 5059 mothers completed a Child Behavior Checklist and provided information on their child's school progress. A total of 5051 adolescents completed a Youth Self Report, with 3703 also undergoing psychometric testing with Ravens Progressive Matrices and Wide Range Achievement Test (WRAT) reading subtest. Outcomes were compared on the basis of birth weight groups and measures of body symmetry and were adjusted for the level of social risk at birth. RESULTS: Adolescents who were born small for gestational age (SGA), when compared with their appropriately grown counterparts (>10th percentile), were more likely to experience learning difficulties, with a higher prevalence in those of birth weight < or =3rd percentile. Girls of birth weight < or =3rd percentile were more likely to have attentional problems and low WRAT reading scores. There was no significant difference in Ravens IQ or mean WRAT reading scores between SGA and non-SGA groups. There was no association between body symmetry and any of the outcomes studied. CONCLUSIONS: SGA status seems to have only modest independent effects on learning, cognition, and attention in adolescence. Severity but not symmetry of growth restriction predicted learning difficulties.